The Relationship between Roblox Game Addiction and Religiosity Values among Adolescents - Sabrina, Filza Nur; Tumin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2026)
The emergence of the metaverse has blurred the boundaries between physical and virtual realities. In this era of rapid digital globalization, metaverse platforms such as Roblox have become increasingly integrated into adolescents’ daily lives and educational environments, offering new opportunities while also presenting complex ethical challenges. This study aims to examine the empirical impact of Roblox game addiction on the religious values of students at SMA Muhammadiyah 1 Bantul. Employing a quantitative research approach, data were collected through questionnaires administered to 36 active Roblox players selected using purposive sampling. The data were analyzed using Pearson correlation and simple linear regression. The findings reveal that excessive engagement with Roblox significantly contributes to disrupted sleep patterns and the neglect of religious obligations, ultimately leading to a decline in students’ moral discipline and akhlak (Islamic moral character). These findings highlight the critical importance of integrating strong moral and ethical values into adolescents’ digital lives. The study also offers important implications for two educational contexts. In Islamic educational institutions, the results underscore the urgent need to strengthen discipline in religious practices, particularly performing prayers on time, while fostering commendable moral character. In general education settings, the findings are equally relevant for addressing the erosion of adolescent character associated with excessive digital engagement. Specifically, they emphasize the importance of promoting effective time management, maintaining healthy sleep patterns, and cultivating responsible digital behavior by reducing exposure to negative emotions and toxic interactions on online platforms. Abstrak: Kemunculan metaverse, telah mengubah batas antara realitas fisik dan virtual. Dalam era globalisasi yang dinamis, teknologi metaverse seperti Roblox telah memasuki sektor pendidikan dan kehidupan remaja, memberikan peluang baru serta tantangan dalam aspek etika. Penelitian ini bertujuan untuk mengeksplorasi dampak kecanduan game Roblox terhadap nilai-nilai religius siswa di SMA Muhammadiyah 1 Bantul. Dengan pendekatan metode campuran, data diperoleh melalui kuesioner yang diisi oleh 36 siswa yang dipilih dengan teknik purposive sampling. Analisis data dilaksanakan menggunakan metode regresi linier sederhana dan korelasi Pearson. Temuan ini menunjukkan bahwa waktu bermain yang berlebihan dapat menyebabkan gangguan pola tidur dan pengabaian tanggung jawab ibadah, yang berdampak pada penurunan disiplin moral dan akhlak siswa. Penelitian ini merekomendasikan pentingnya pengintegrasian prinsip moral serta konsekuensi signifikan yang dapat diterapkan dalam dua aspek pendidikan. Dalam konteks sekolah yang berlandaskan pada ajaran Islam, temuan ini mendasari kebutuhan mendesak untuk memperkuat disiplin dalam menjalankan ibadah ritual (seperti melaksanakan shalat tepat waktu) dan membentuk akhlak terpuji. Sementara itu, dalam konteks pendidikan yang lebih umum (sekolah biasa), hasil dari penelitian ini masih sangat relevan untuk menangani penurunan karakter remaja akibat pengaruh dunia maya, khususnya dalam hal memperbaiki pengelolaan waktu, menjaga pola tidur (sirkadian) siswa, serta menyaring emosi negatif atau perilaku tidak etis (toxic) saat berinteraksi di platform digital.